2015
DOI: 10.1634/theoncologist.2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status, Body Surface, and Low Lean Body Mass/Body Mass Index Are Related to Dose Reduction and Severe Gastrointestinal Toxicity Induced by Afatinib in Patients With Non-Small Cell Lung Cancer

Abstract: Background. The main reason for dose reduction of afatinib is gastrointestinal toxicity (GT). In a phase II study, we analyzed anthropometrical, nutritional, and biochemical factors associated with GT induced by afatinib. Materials and Methods. Patients diagnosed with non-small cell lung cancer who progressed to prior chemotherapy received 40 mg of afatinib. Malnutrition was determined by Subjective Global Assessment, and lean body mass (LBM) was determined by computed tomography scan analysis using a pre-esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 28 publications
2
73
1
4
Order By: Relevance
“…There were also no significant differences in PFS based on baseline BSA or BMI in either study. Similarly, a phase II study assessing the effect of malnutrition and BSA on afatinib-related AEs found that PFS was not significantly different in patients with or without dose reduction [median 9.2 versus 14.6 months (P = 0.337)] [19]. Overall, these findings suggest that tolerability-guided dose modification does not affect the efficacy of afatinib and, once the dose has been optimized for the individual patient, substantial clinical benefit is obtained.…”
Section: Efficacymentioning
confidence: 83%
“…There were also no significant differences in PFS based on baseline BSA or BMI in either study. Similarly, a phase II study assessing the effect of malnutrition and BSA on afatinib-related AEs found that PFS was not significantly different in patients with or without dose reduction [median 9.2 versus 14.6 months (P = 0.337)] [19]. Overall, these findings suggest that tolerability-guided dose modification does not affect the efficacy of afatinib and, once the dose has been optimized for the individual patient, substantial clinical benefit is obtained.…”
Section: Efficacymentioning
confidence: 83%
“…First of all, organized strategies for screening, diagnosis, and treatment are generally not implemented; second, there is very limited access to target therapies due to high prices, lack of insurance, or for social reasons; and finally, screening for specific mutations is not routinely performed [19, 30]. All of these factors contributed to the creation of this consortium and the conduction of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, muscle wasting and low muscle mass have been linked to poorer survival and increased risk of treatment toxicity in various cancer diagnoses, including NSCLC 15, 16, 17, 18, 19. In advanced NSCLC, a recent study from our group showed that low muscle mass was a significant predictor for chemotherapy‐induced haematological toxicity 20…”
Section: Introductionmentioning
confidence: 99%